2019
DOI: 10.1109/tbme.2018.2886681
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference-Based Estimation of Normal Aortic, Aneurysmal and Atherosclerotic Tissue Mechanical Properties: From Material Testing, Modeling and Histology

Abstract: Objective: Mechanical properties of healthy, aneurysmal, and atherosclerotic arterial tissues are essential for assessing the risk of lesion development and rupture. Strain energy density function (SEDF) has been widely used to describe these properties, where material constants of the SEDF are traditionally determined using the ordinary least square (OLS) method. However, the material constants derived using OLS are usually dependent on initial guesses. Methods: To avoid such dependencies, Bayesian inference-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The estimation of the mechanical properties may provide rich information to identify plaque vulnerability, such as whether an atherosclerotic coronary artery suffers from a reduced collagen synthesis, local overexpression of collagenase, or smooth muscle cell apoptosis ( Libby, 2001 ; Akyildiz et al., 2011 ; Davis et al., 2016 ; Wang et al., 2019 ; O’Reilly et al., 2020 ). This information can also be used to evaluate the impact of different drugs in treating atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of the mechanical properties may provide rich information to identify plaque vulnerability, such as whether an atherosclerotic coronary artery suffers from a reduced collagen synthesis, local overexpression of collagenase, or smooth muscle cell apoptosis ( Libby, 2001 ; Akyildiz et al., 2011 ; Davis et al., 2016 ; Wang et al., 2019 ; O’Reilly et al., 2020 ). This information can also be used to evaluate the impact of different drugs in treating atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, an approach performed with adult mini-pigs prone to atherosclerosis showed that necrotic core sizes determined by virtual and real histology were different, thus questioning the capacity of virtual histology to detect prone plaques ( Thim, 2010 ). Moreover, none of these techniques have the capacity to quantify the mechanical properties of the arterial wall, which is essential to estimate stress distribution ( Akyildiz et al., 2011 ; Wang et al., 2019 ). One promising approach is the iMOD elastography ( Le Floc’h et al., 2010 ), which developed several computational algorithms to rebuild elasticity strain maps inside the wall based on the prediction of the stress maps using IVUS-derived techniques.…”
Section: Introductionmentioning
confidence: 99%